Influence of processing parameters on the properties of tin coatings deposited on tool steels using cathodic arc physical vapour deposition technique - Ali, Mubarak (2007)

(untitled)
Titanium nitride (TiN) which is widely used as a hard coating material, was coated on two types of tool steels, the high-speed steel (HSS) and D2 tool steel, by physical vapour deposition method. The study concentrated on cathodic arc physical vapour deposition (CAPVD), a technique used for the deposition of hard coatings for tooling applications, and which has many advantages. The main drawback of this technique, however, is the formation of macrodroplets (MD’s) during deposition, resulting in films with rougher morphology. The presence of MD’s in CAPVD process is a serious problem during practical tooling applications. Various standard characterization techniques and equipments, such as electron microscopy, X-rays, atomic force microscopy, hardness testing machine, scratch tester and pin-on-disk machine, were used to analyze and quantify the following properties and parameters: surface morphology, thickness, crystallography, hardness, adhesion and coefficient of friction of the deposited coatings. The MD’s contamination and growth mechanisms were investigated as a function of metal ion etching, substrate bias, and nitrogen flow rate. The results showed that the nitrogen flow rate was the most important factor in controlling the size and number of the MD’s. Three-dimensional AFM images and electron microscopy indicated that the MD’s were generated during the etching stage and protruded through the TiN film during deposition process. For 90 minutes coating time, the TiN coating thickness decreased from 7.1 to 5.7 µm due to re-sputtering of the growing film as the bias voltage is increased from zero to -150 V. The coatings deposited with Cr ion etching for 8 and 16 minutes caused a reduction of 50% hardness compared to the samples etched with Ti for similar etching times. Both coating thickness and indentation loads influenced the hardness of the deposited coating. Chromium ion etching significantly reduced the surface roughness, hardness, and friction coefficient compared to titanium ion etching. The coatings deposited on HSS exhibited better adhesion compared to those on D2 tool steel.